(untitled) (The Review of Diabetic Studies, 2025)
This research aims to study the effectiveness of air ambulance units in reducing mortality rates resulting from traffic accidents occurring in areas remote from urban centers in the Kingdom of Saudi Arabia. The researcher used a 12-item questionnaire to measure participants’ views on the speed of response, readiness of medical equipment, field coordination, and the level of satisfaction of injured people and their families with the services provided. The statistical results showed that the overall average of responses was 4.14, indicating a high level of agreement on the effectiveness of air ambulance units. Pearson correlation analysis also showed statistically significant relationships between all study dimensions, with response speed, equipment readiness, and field coordination being positively correlated with overall satisfaction. These findings indicate that enhancing integration between air and ground ambulance teams, and equipping units with modern technologies and specialized training, directly contributes to improving the quality of emergency services and reducing deaths in remote areas. The study recommends increased investment in air ambulance infrastructure and expanding its operations to cover wider areas, ensuring equitable provision of emergency healthcare between urban and rural populations.